Internet connectivity disruption in Canada (Canada) - Voidly (2026)
CRITICAL severity disruption detected in Canada. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: CA-2026-0006
Keywords: internet disruption; CA; disruption; critical